Strategic Management Analisys of PT Asiapapercon Internusa - Nurul Qurnias; Yesika Magdalena; Riza Oktavania Trianggono; Intan Nabila; Tiara Puspa (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
The carton packaging industry in Indonesia is experiencing significant growth in line with increasing demand in the manufacturing, food and beverage, and e-commerce sectors. PT. Asiapapercon Internusa is a company engaged in the production of corrugated carton boxes, which plays a vital role in the industrial supply chain. This study aims to analyze PT. Asiapapercon Internusa's business strategy and competitiveness in facing increasinglycompetitive industry conditions. The research method used is a qualitative descriptive approach, with data collection techniques through interviews, observations, and documentation studies. Analytical tools used include SWOT analysis, PESTEL analysis, and Porter's Five Forces analysis. The results indicate that PT. Asiapapercon Internusa has advantages in product quality standards, international certification, and long-term relationships with major customers. However, the company still faces challenges in operational digitalization and dependence on fluctuating raw material prices. Recommended strategies include strengthening product differentiation, operational digitalization, and developing environmentally friendly packaging.